Neonatal outcomes in preterm infants with severe congenital heart disease: a national cohort analysis - Aly, Safwat; Qattea, Ibrahim; Kattea, Mohammad O.; Aly, Hany Z. (Frontiers in Pediatrics, 2024)
Background: Prematurity and congenital heart disease (CHD) are the leading causes of neonatal mortality and morbidity. Limited data are available about the outcomes of premature infants with severe CHD.We queried The National Inpatient Database using ICD-10 codes for premature patients (<37 weeks) with severe CHD from 2016-2020. Severe CHDs were grouped into three categories: A. left-sided lesions with impaired systemic output, B. Cyanotic CHD, and C. Shunt lesions with pulmonary overcirculation. Patients with isolated atrial or ventricular septal defects and patent ductus arteriosus were excluded. We also excluded patients with chromosomal abnormalities and major congenital anomalies. Patients' demographics, clinical characteristics, and outcomes were evaluated by comparing premature infants with versus without CHD adjusting for gestational age (GA), birth weight, and gender.Results: A total of 27710 (1.5%) out of 1,798,245 premature infants had severe CHD. This included 27%, 58%, and 15% in groups A, B, and C respectively. The incidence of severe CHD was highest between 25 and 28 weeks of gestation and decreased significantly with increasing GA up to 36 weeks (p<0.001). Premature infants with severe CHD had a significantly higher incidence of neonatal morbidities including necrotizing enterocolitis (NEC) [OR = 4.88 (4.51-5.27)], interventricular hemorrhage [OR=6.22 (5.57-6.95)], periventricular leukomalacia [OR=3. 21 (2.84-3.64)] and bronchopulmonary dysplasia compared to preterm infants of similar GA without CHD. Shunt lesions had the highest incidence of NEC (8.5%) compared to 5.3% in cyanotic CHD and 3.7% in left-sided lesions (p<0.001). Mortality was significantly higher in premature infants with CHD compared to control [11.6% vs 2.5%, p< 0.001]. Shunt lesions had significantly higher mortality (11.0%) compared to those with left-sided lesions (8.3%) and cyanotic CHD (6.4%), p<0.001.Premature infants with severe CHD are at high risk of neonatal morbidity and mortality.Morbidity remains increased across all GA groups and in all CHD categories. This significant risk of adverse outcomes is important to acknowledge when managing this patient population and when counseling their families. Future research is needed to examine the impact of specific rather than categorized congenital heart defects on neonatal outcomes.